Réponse:
a) (2x + 3)(x - 4) = 2x² - 8x + 3x - 12 = 2x(x - 4) + 3(x - 4) = (x - 4)(2x + 3)
b) (3a + 5)(2a - 1) = 6a² - 3a + 10a - 5 = 3a(2a - 1) + 5(2a - 1) = (2a - 1)(3a + 5)
c) (4x + 1)(x + 2) = 4x² + 8x + x + 2 = 4x(x + 2) + (x + 2) = (x + 2)(4x + 1)
d) (5y - 2)(3y + 6) = 15y² + 30y - 6y - 12 = 15y(y + 2) - 6(y+2) = (y + 2)(15y - 6)
Copyright © 2025 ELIBRARY.TIPS - All rights reserved.
Lista de comentários
Réponse:
a) (2x + 3)(x - 4) = 2x² - 8x + 3x - 12 = 2x(x - 4) + 3(x - 4) = (x - 4)(2x + 3)
b) (3a + 5)(2a - 1) = 6a² - 3a + 10a - 5 = 3a(2a - 1) + 5(2a - 1) = (2a - 1)(3a + 5)
c) (4x + 1)(x + 2) = 4x² + 8x + x + 2 = 4x(x + 2) + (x + 2) = (x + 2)(4x + 1)
d) (5y - 2)(3y + 6) = 15y² + 30y - 6y - 12 = 15y(y + 2) - 6(y+2) = (y + 2)(15y - 6)